Asupan makan DASH-like diet untuk mencegah risiko hipertensi pada wanita prediabetes - Ayu Rahadiyanti; Budi Yuli Setianto; Martalena Br Purba (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2015)
Background: Prediabetics have cardiovascular risk factors such as obesity, hypertension, and dyslipidemia. Unhealthy food intake can increase the risk of hypertension in prediabetes. Prediabetes hypertension has the impact on increasing prevalence of diabetes and cardiovascular disease. A cohort study has shown that DASH diet is related to the lower incidence of hypertension in women (1).Objective: Of this study had the purpose to know that inappropriate DASH-like diet intake is associated with hypertension risk at prediabetes women in Puskesmas Tlogosari Kulon Semarang.Method: A cross-sectional study was conducted in Puskesmas Tlogosari Kulon area on January – March 2014 among 117 prediabetes women. The subjects were selected using consecutive sampling. Independent variable in this study was DASH-like diet intake which assessed from FFQ and the dependent variable was hypertension risk. The subject was classified as at risk for hypertension if, in seated position, the mean of the two measurements was ≥120/80 mmHg. Chi-Square test and logistic regression were used to analyze the data.Results: The mean of DASH-like diet score in subjects who were not at hypertension risk (3.31) was higher than subjects who were at hypertension risk (3.23). There was 90,77% person with hypertension risk who did not consume DASH-like diet properly. But the association of DASH-like diet intake with hypertension risk was not significant (p=0.194). The multivariate result showed that there was association between family history (p=0.047), obesity (p=0.016), and fat intake (p=0.015) with hypertension risk.Conclusion: Inappropriate DASH-like diet intake may increase the risk of hypertension, but it is not statistically significant.